Svakīyātvanirāśavicāraḥ tathā Parakīyātvanirūpaṇaṃ - Viśvanātha Cakravartin (Gauḍīyagranthagauravaḥ ;, 1963)
Two treatises on the poetic characteristics of Rādhā, Hindu deity, according to the Gaudiya Vaishnavite point of view.